Tailoring cell-inspired biomaterials to fuel cancer therapy - Qi-Hui Wang; Shi Cheng; Chun-Yu Han; Shuang Yang; Sheng-Rui Gao; Wan-Zhong Yin; Wen-Zhi Song (Materials Today Bio)
Cancer stands as a predominant cause of mortality across the globe. Traditional cancer treatments, including surgery, radiotherapy, and chemotherapy, are effective yet face challenges like normal tissue damage, complications, and drug resistance. Biomaterials, with their advantages of high efficacy, targeting, and spatiotemporal controllability, have been widely used in cancer treatment. However, the biocompatibility limitations of traditional synthetic materials have restricted their clinical translation and application. Natural cell-inspired biomaterials inherently possess the targeting abilities of cells, biocompatibility, and immune evasion capabilities. Therefore, cell-inspired biomaterials can be used alone or in combination with other drugs or treatment strategies for cancer therapy. In this review, we first introduce the timeline of key milestones in cell-inspired biomaterials for cancer therapy. Then, we describe the abnormalities in cancer including biophysics, cellular biology, and molecular biology aspects. Afterwards, we summarize the design strategies of cell-inspired antitumor biomaterials. Subsequently, we elaborate on the application of antitumor biomaterials inspired by various cell types. Finally, we explore the current challenges and prospects of cell-inspired antitumor materials. This review aims to provide new opportunities and references for the development of antitumor cell-inspired biomaterials.